Application of diffractive lens arrays in confocal microscopy - Li , Zheng (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2022)
Diffractive lens arrays are proposed in this work for application in reflected-light confocal microscopes. They have overcome the limitations between fields of view and resolution of traditional objectives. Experiments of multi-spot confocal imaging in surface metrology and fluorescence microscopy have been demonstrated based on the proposed concepts, which have shown capabilities of high-resolution measurement over a large area.